Analysis of Imbalance Between Government Regulations and Nursing Education on Industrial Nurses - Syaifoel Hardy; Asep Hermawan Sanudin; Ridha Afzal; Isak JHTukayo (Caring: Indonesian Journal of Nursing Science, 2021)
In Indonesia, industrial nurses are only required to have an Occupational Safety and Health (K3) certificate up to this time. This policy is not in line with Law No. 36/2014. As a result, there is an imbalance between industry needs for quality nursing services and existing nurses' competence. This study aimed to analyze policies related to the competencies of corporate nurses in meeting the needs of health care services in the industry. This study used PRISMA Flow Diagram as a systematic review supported by quantitative descriptive design. The research was conducted through document searches, identifying keywords, and reviewing articles from Google Scholar (6 records), Research Gate (8 records), and PubMed (5 records), and others were 52 records. Out of 71 documents, 36 records were assessed for eligibility, and 35 records were excluded, and 16 studies were included in the review. It was found that there was an imbalance between the regulations, education programs, and implementation. It requires the strengthening of a multisectoral approach in the development of OH nursing education.